Electrophysiologic and molecular characterization of membrane anionic transporters in pollen tubes - Dias, Pedro Nuno Resende (2015)
Tese de doutoramento, Biologia (Biologia do Desenvolvimento), Universidade de Lisboa, Faculdade de Ciências, 2015